1974
DOI: 10.1017/s0317167100019569
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Hypothalamic Neurons and of the Median Eminence

Abstract: SUMMARYOur light, and electron microscopic (EM) findings within the hypothalamic supraoptic (SO) and paraventricular (PV) nuclei of the normal female rabbit are in agreement with those reported earlier by other investigators for the same nuclei of the dog and rat. The neurons of these nuclei are the hypothalamic synthesis sites of the neurohypophyseal hormones.With the exception of the arcuate nucleus, none of the hypothalamic nuclei associated with the control of adenohypohpyseal function have been studied ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…HRP staining demonstrated three different types of cell in the v.m.h., based on dendritic arborization and soma size, and this classification was correlated with membrane properties. Early anatomical studies (Wahren, 1959;Clattenburg, 1974) reported that v.m.h. neurones were of a single type.…”
Section: Morphology and Glucose Responsivenessmentioning
confidence: 99%
“…HRP staining demonstrated three different types of cell in the v.m.h., based on dendritic arborization and soma size, and this classification was correlated with membrane properties. Early anatomical studies (Wahren, 1959;Clattenburg, 1974) reported that v.m.h. neurones were of a single type.…”
Section: Morphology and Glucose Responsivenessmentioning
confidence: 99%
“…According to light and electron microscopic investigations, the ME has a layered structure [ 62 , 63 , 64 , 65 , 66 , 67 , 68 ]. This structure contains nerve terminals, glial cells, and capillaries, but there are no synapses.…”
Section: Structure Of the Mementioning
confidence: 99%